62‐2: Ultra‐flat, Low‐density, and High‐refractive‐index Glass Wafers for Augmented Reality: Weight Reduction as Key Enabler for Consumer Devices. Issue 1 (28th June 2022) - Bachhuber, Frederik; Sprengard, Ruediger; Jotz, Matthias; Ottermann, Clemens; Weidlich, Stefan; Schreder, Bianca; Deneke, Lenka; Claussen, Olaf; Lu, Zhengyang; Wang, Alex; Wan, Congshan
Abstract : Planar high‐refractive‐index glass wafers are the backbone of leading Augmented and Mixed Reality devices. They route the virtual image to the user's eye, while helping to keep the form factor small. While the glass characteristics directly affect fundamental design parameters such as field of view, the optical system of the wafer with its interfaces as a whole determines the image quality. Here we report on latest achievements both on the glass and on the wafer level that allow for significant weight reduction without sacrificing optical performance. Based on a state‐of‐the‐ art two layer device with a refractive index of 1.9, an overall weight reduction >20% is feasible. This creates a basis to drive AR devices from niche applications toward more widespread commercial adoption.